2022
DOI: 10.1039/d2fo01945k
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of the olive tree and its derivatives on the skin

Abstract: The olive tree and its derivatives are of great interest in the field of biomedicine due to their numerous health properties. The aim of the present study was to identify...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 127 publications
(217 reference statements)
2
4
0
Order By: Relevance
“…Additionally, a decrease in the expression of inflammatory markers such as IL-6 and IL-1α in response to ZP treatment was observed. These results are consistent with previous research highlighting the anti-inflammatory and antioxidant potential of phenolic compounds in skin cells [51,52,84,89]. Moreover, the negative modulation of AhR and Nrf2 by ZP suggests a potential interference in key signaling pathways related to oxidative stress.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, a decrease in the expression of inflammatory markers such as IL-6 and IL-1α in response to ZP treatment was observed. These results are consistent with previous research highlighting the anti-inflammatory and antioxidant potential of phenolic compounds in skin cells [51,52,84,89]. Moreover, the negative modulation of AhR and Nrf2 by ZP suggests a potential interference in key signaling pathways related to oxidative stress.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, there is a strong demand for good photo-protectors that can enhance the natural cutaneous pigmentation in the skin. In this context, olive extract and its major components were studied for their effects on melanogenesis and photoprotection [52][53][54]. However, previously, the effects of OL and OC on the skin were barely known.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the many health benefits of olives, the specific effects of the individual olive component on the skin have yet to be studied intensively. Nevertheless, recent studies have reported the anti-inflammatory effect and UV protection effects of olive extract [52][53][54]. Building on those findings, in this study, we aimed to screen the effects of three olivederived compounds (OP, OL, and OC) on melanin production through mouse melanoma B16F10 cells, which originate from melanocytes and human epidermal melanocytes.…”
Section: Introductionmentioning
confidence: 99%
“…HvOle can be potentially used as an antioxidant for the reduction of the effects of oxidative stress on the skin and possibly preventing skin aging. The increasing consumers’ demand for green and natural compounds in view of their safer and healthier properties with respect to synthetic products is supporting the development of antioxidants of natural origin in several fields, including cosmetics. In this context, lipophenols show an increased skin penetration capacity compared to their polar parent phenolics. Their lipophilicity plays a role in increasing their antimicrobial, antioxidant, or antiaging properties. ,,,,, …”
Section: Discussionmentioning
confidence: 99%